Upper respiratory tract infection in athletes: Influence of lifestyle, type of sport, training effort, and immunostimulant intake - König, D.; Grathwohl, D.; Weinstock, Ch.; Northoff, H.; Berg, B. (Exercise Immunology Review, 2000)
Epidemiological evidence suggests that heavy acute or chronic exercise is related to an increased incidence of upper respiratory tract infections in athletes, while moderate exercise is believed to be protective. During the past years, many groups have investigated the association between changes within the immune system and exercise at different intensity levels. Although following strenuous exercise, some immunologic alterations were quite consistent and reproducible, e.g. neutrophilia, lymphopenia, and depression of natural killer cell activity, some findings were divergent or strongly dependant on the study design and athletes investigated. Lately, interesting results in the field of psychoneuroimmunolgy as well as new insights in the relationship between macro- and micronutrient and the immune system have brought up new fields of research interest. There is growing evidence that e.g. lifestyle factors, the coping with daily stress, and dietary behavior are important cofactors in the immune response to exercise. The present work gives a short review on the literature dealing with URTI in athletes with special reference to the above mentioned cofactors. In addition, the results of a recent investigation concerning training and associated lifestyle patterns in German athletes are presented.